When the Boys Come Home - Evans, Pamela (London Headline, 2007)
As German bombs wreak havoc on West London, residents have little choice but to carry on with their daily lives, and for Morgan's Dairy it's business as usual. But when Megan Stubbs' father, Dai Morgan, is killed in an air raid, she is devastated. Coping with her loss, Megan is determined to continue the tradition of which Dai was so proud, and, with her mother, Dolly, she braves the ravaged streets to do the milk round by horse and cart. Megan finds comfort in the knowledge that her twin girls have been evacuated and are safely tucked away in a Welsh village with her sister Hetty and Hetty's little boy. But Megan worries constantly about her husband, Will. abroad with his platoon. And when Will's life-long friend, Doug Reynolds, returns, wounded, and disfigured, she doesn't hesitate to take him in. However, Doug is not the man she thinks he is.
Keywords: World War (1939-1945) -- England--London -- Manners and customs